Effect of Pressure Gradient on Flow and Heat Transfer over Surface-Mounted Heated Blocks in a Narrow Channel - Gürses, Dildar; Pulat, Erhan (Applied sciences, 2025)
In this study, pressure gradient effects on heat transfer from block-like electronic chips are investigated computationally. The pressure gradient is provided by the slope given to the upper plate and starts just before the first block. Tilt angles of −2°, 0°, 2°, 4° and 6° have been used. Air is used as the fluid, and it enters the duct at a constant speed with a uniform velocity profile. Calculations were made for Re numbers (Re = 6000, 9015, and 11,993) defined according to the channel height. For this purpose, conservation and SST k-ω turbulence model equations are solved by using ANSYS-Fluent 20.1 software for two-dimensional, incompressible, and turbulent flow conditions. Velocity, temperature, pressure, and turbulence kinetic energy distributions were obtained and compared for the considered slope angles. The effects of all changing conditions on heat transfer were discussed by calculating local and average Nusselt values, the reattachment lengths after the last block were calculated by plotting, and a comparison was made by plotting the pressure values on the block in the middle of the channel and at the top of the channel.